Pengaruh antara Dukungan Sosial Teman Sebaya dan Penyesuaian Diri pada Santri Baru di Pondok Pesantren Surabaya - Eryn Uma Rizka; Siti Jaro'ah (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Self-adjustment is a crucial ability that determines the success of new students in adapting to the environment of Islamic boarding schools, which differ from their home life in terms of rules, values, and social interaction patterns. This transition often creates emotional and social challenges that can affect students’ psychological well-being. The purpose of this study was to examine the effect of peer social support on the self-adjustment of new students at three Islamic boarding schools in Surabaya. The research employed a quantitative approach with a correlational design involving 101 new students who had lived in dormitories for less than six months. The results showed that peer social support had a positive and significant effect on self-adjustment (r = 0.530; p < 0.001; R² = 0.281). Students who received emotional, acceptance, and tangible support from peers demonstrated better adaptation in social, academic, and spiritual domains. These findings support Cohen and Hoberman’s theory that social support acts as a psychological buffer in stressful adaptation processes. Furthermore, the study highlights the importance of interpersonal relationships in enhancing students’ well-being. The implications suggest the need for developing peer-based counseling and support programs to help new students adapt more effectively within Islamic boarding school environments.